Economic Value of Vector-Borne Dengue Fever Mitigation Cheras Malaysia - Tee, Chee Hong (2011)
Rapid industrial and economic development in Malaysia over the last two decades has brought about development, creating prevalence of vector-borne diseases, such like dengue fever. Dengue fever has increased dramatically in Malaysia from less than 1000 cases in 1973 to 41486 cases in 2009. Latest Press Release of Dengue Fever & Chikungkunya Situation in Malaysia Week 49/2010 (5 - 11 Dec 2010) from Director General of Health Malaysia reported that there is total 44,641 dengue cases reported and 132 people die from dengue fever. Selangor state reported as the highest which is 15,862 dengue cases 44 dead cases reported in Week 49/2010 mainly because dengue often occurs in urban and semi urban area. Furthermore, there is no effective vaccine or drug treatment for dengue fever. Hence, the adverse health effects should not be overlooked. The prime aim of this study is to estimate monetary value of the externalities (nonmarket values) associated with vector borne dengue fever mitigation. Therefore this study will assess the economic value using the contingent valuation method (CVM). A pilot test is conducted to determine the bids of the payment card by eliciting the willingness to pay (WTP) using the open-ended questionnaire then ranked the WTP of these valid samples and selected 20th, 40th, 60th, and 80th percentiles to be the designated bids in the real survey. A face-to-face interview approach was being conduct in this paper. The respondent’s WTP is investigated in the survey using the open-ended payment card approach, and the results show that Selangor’s households would pay RM4.16 per month per household (RM49.92 per year per household) for immediate efforts to mitigate rise in dengue fever epidemics. Therefore for the entire society of Selangor’s households, the economic value is RM49.7 million (US$13.08 million) per year. These findings show that the respondents are concerned with the dengue fever epidemic. In other words, people are willing to pay significant money to avoid the increase in dengue fever cases. The figure above can be used as a fundamental for the local government to compute the medical treatment cost for dengue fever which is rising rapidly. In addition, government could use such a budget for mitigation and adaptation strategy to reduce the prevalence of vector-borne diseases, such like dengue fever.